ANALISIS GENDER TENTANG KONSEP WALI NIKAH MENURUT KOMPILASI HUKUM ISLAM - Icep Maulana Zatnika; Muhammad Nurcholis (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2019)
The role of the marriage guardian in marriage is very important and decisive, as stipulated in Article 19 Compilation of Islamic Law, which states that, the marriage guardian in marriage is a harmony that must be fulfilled for the prospective bride who acts to marry her. In Article 20 The person acting as a guardian of marriage is a man who fulfills the requirements of Islamic law namely Muslim, aqil and baligh and the guardian of the marriage consists of: Trustee and guardian of the judge. In the Compilation of Islamic Law the articles on guardianship are patriarchal bias and are still less responsive to women's interests. A gender inequality regarding the concept of marriage guardianship is further strengthened by the provisions of the guardian of marriage. In the Compilation of Islamic Law which is explicitly only shown to men. As in the Compilation of Islamic Law article 20 paragraph states explicitly, that who acts as a guardian of marriage is a man. Problems Gender differences are not a problem as long as they do not create gender inequality. But it turns out that gender differences have given rise to various injustices. Researchers tried to formulate a problem about how the guardian of marriage according to the Compilation of Islamic Law and gender analysis on the concept of guardian marriage according to the Compilation of Islamic Law. Method This study uses a gender perspective qualitative text in which research to be conducted is based on library data relating to the subject matter being discussed. This research includes qualitative research so that the data data is expressed as the original. The results of this study are that the concept of guardian marriage in the Compilation of Islamic Law if approached through a gender approach and fiqh proposal will get a meeting point, namely that people who have the ability to act perfectly both men both men and women, they do not need a guardian, they can even be guardians for people who really need and deserve to be under their guardianship. The guardian of marriage in the Compilation of Islamic Law still does not provide equal opportunities for all human beings without discrimination on the basis of sex, then in the Islamic Law Compilation the articles on marriage guardians are still less responsive to the interests of women and guardians of marriage. analyzed with a gender perspective. Because the guardian of marriage in the Compilation of Islamic Law has not reflected the basic principles of justice and gender equality. The concept of guardian marriage in the Compilation of Islamic Law still seems patriarchal bias which tends to weaken women